Facility for Customizing Transaction Forms on Master Data Using an Online Accounting System Web For Work Efficiency Company - Sudaryono, Sudaryono; Sunarya, Lusyani; Maulani, Giandari (APTISI Transactions on Management (ATM), 2017)
In the online accounting system based on a website that is very sophisticated and growing, complete facilities are certainly needed to support the smoothness and ease of accountants to apply to a company's finance. as in most other list facilities in the online accounting data master system is very influential in the ease of application consists of several features such as managing tax, warehouse list, changing product units, and terms and method of payment of the transaction itself. as an example of this tax regulating feature, it is very important, because it serves to direct and display a list of the types of taxes that the company uses for sales transactions to customers or purchases to company suppliers. then for the warehouse list is also important with other features in the master data facility that is to monitor warehouses or can be referred to as the branch of the company that you noted in your company's online accounting. To change product units can make it easier to describe the number of products available in the company, such as dozen samples, packages, boards, fruits, and pcs. the terms and method of payment in this menu function to create new and display the payment methods used by your company to your suppliers when making transactions. So, with the facilities in the master data can facilitate and provide work efficiency in shortening the flow and process on the features available in the master data facility. Keywords​: ​Master Data, Register Warehouse, Change Products, and Payment Method​.